FRANK UPWARD, BARBARA REED, GILLIAN OLIVER, and JOHANNE EVANS, Recordkeeping Informatics for a Networked Age - Alaoui, Siham (Archivaria, 2019)
Recordkeeping Informatics for a Networked Age. Frank Upward, Barbara Reed, Gillian Oliver, and Johanne Evans. Clayton, Victoria: Monash University Publishing, 2018. xxv, 288 pp. ISBN 978-1925495881